Identifying the microtearing modes in the pedestal of DIII-D H-modes using gyrokinetic simulations. (17th December 2021) - Hassan, Ehab; Hatch, D.R.; Halfmoon, M.R.; Curie, M.; Kotchenreuther, M.T.; Mahajan, S.M.; Merlo, G.; Groebner, R.J.; Nelson, A.O.; Diallo, A.
Abstract: Recent evidence points toward the microtearing mode (MTM) as an important fluctuation in the H-mode pedestal for anomalous electron heat transport. A study of the instabilities in the pedestal region carried out using gyrokinetic simulations to model an ELMy H-mode DIII-D discharge (USN configuration, 1.4 MA plasma current, and 3 MW heating power) is presented. The simulations produce MTMs, identified by predominantly electromagnetic heat flux, small particle flux, and a substantial degree of tearing parity. The magnetic spectrogram from Mirnov coils exhibits three distinct frequency bands—two narrow bands at lower frequency (∼35–55 kHz and ∼70–105 kHz) and a broader band at higher frequency (∼300–500 kHz). Global linear GENE simulations produce MTMs that are centered at the peak of the ω * profile and correspond closely with the bands in the spectrogram. The three distinctive frequency bands can be understood from the basic physical mechanisms underlying the instabilities. For example (i) instability of certain toroidal mode numbers ( n ) is controlled by the alignment of their rational surfaces with the peak in the ω * profile, and (ii) MTM instabilities in the lower n bands are the conventional collisional slab MTM, whereas the higher n band depends on curvature drive. While many features of the modes can be captured with the local approximation, a global treatment is necessary to quantitatively reproduce the detailed band gaps of the low- n fluctuations. Notably, the transport signatures of the MTM are consistent with careful edge modeling by SOLPS.